Immunization with a heat-killed bacterium, Mycobacterium vaccae NCTC 11659, prevents the development of cortical hyperarousal and a PTSD-like sleep phenotype after sleep disruption and acute stress in mice. Issue 6 (7th December 2020) - Bowers, Samuel J; Lambert, Sophie; He, Shannon; Lowry, Christopher A; Fleshner, Monika; Wright, Kenneth P; Turek, Fred W; Vitaterna, Martha H
Abstract: Study Objectives: Sleep deprivation induces systemic inflammation that may contribute to stress vulnerability and other pathologies. We tested the hypothesis that immunization with heat-killed Mycobacterium vaccae NCTC 11659 (MV), an environmental bacterium with immunoregulatory and anti-inflammatory properties, prevents the negative impacts of 5 days of sleep disruption on stress-induced changes in sleep, behavior, and physiology in mice. Methods: In a 2 × 2 × 2 experimental design, male C57BL/6N mice were given injections of either MV or vehicle on days –17, –10, and –3. On days 1–5, mice were exposed to intermittent sleep disruption, whereby sleep was disrupted for 20 h per day. Immediately following sleep disruption, mice were exposed to 1-h social defeat stress or novel cage (control) conditions. Object location memory (OLM) testing was conducted 24 h after social defeat, and tissues were collected 6 days later to measure inflammatory markers. Sleep was recorded using electroencephalography (EEG) and electromyography (EMG) throughout the experiment. Results: In vehicle-treated mice, only the combination of sleep disruption followed by social defeat (double hit): (1) increased brief arousals and NREM beta (15–30 Hz) EEG power in sleep immediately post-social defeat compared to baseline; (2) induced an increase in the proportion of rapid-eye-movement (REM) sleep and number of state shifts for at least 5 days post-social defeat; and (3) induced hyperlocomotion and lack of habituation in the OLM task. Immunization with MV prevented most of these sleep and behavioral changes. Conclusions: Immunization with MV ameliorates a stress-induced sleep and behavioral phenotype that shares features with human posttraumatic stress disorder.